2022
DOI: 10.1155/2022/5314179
|View full text |Cite
|
Sign up to set email alerts
|

An In Silico Study of the Interactions of Alkaloids from Cryptolepis sanguinolenta with Plasmodium falciparum Dihydrofolate Reductase and Dihydroorotate Dehydrogenase

Abstract: The Plasmodium falciparum dihydrofolate reductase (PfDHFR) and dihydroorotate dehydrogenase (PfDHODH) are essential for Plasmodium falciparum growth and development, and have been validated as targets for the development of new antimalarial agents. Several alkaloids isolated from Cryptolepis sanguinolenta have been reported to have antiplasmodial activity, but their protein targets are unknown. Therefore, molecular docking and molecular dynamics simulations were used to investigate the interactions and stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 57 publications
2
10
0
Order By: Relevance
“…Our findings are consistent with those of Erhunse et al regarding the antimalarial effect of isoquinoline alkaloids such as berberine and palmatine [ 42 ]. Kyei et al also demonstrated the potential antimalarial activity of cryptolepine and isocryptolepine [ 43 ]. The display of the potent antiplasmodial activity of the alkaloidal extracts in the present study confirmed earlier reports regarding the diversity of bioactive metabolites and, importantly, the antiplasmodial properties of several classes of alkaloids, such as the indole and isoquinoline classes [ 13 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with those of Erhunse et al regarding the antimalarial effect of isoquinoline alkaloids such as berberine and palmatine [ 42 ]. Kyei et al also demonstrated the potential antimalarial activity of cryptolepine and isocryptolepine [ 43 ]. The display of the potent antiplasmodial activity of the alkaloidal extracts in the present study confirmed earlier reports regarding the diversity of bioactive metabolites and, importantly, the antiplasmodial properties of several classes of alkaloids, such as the indole and isoquinoline classes [ 13 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Each docking experiment was repeated in four technical runs to ensure reproducibility, and in each run, nine poses were generated and ranked according to their binding energies by AutoDock Vina [ 13 ]. Selection of the best poses was based on ligands' binding energy and the ability of the ligands to form optimal interactions with active site residues of the target proteins [ 13 ]. The root mean square deviation of the redocked ligand was calculated in PyMOL.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to this step, Charmm36-july2022 force field for GROMACS was downloaded via Mackerel lab online server. Since GROMACS does not have an internal module for ligand topology file preparation, we relied on CHARMM general force field online server as an external tool to generate the ligand topology file [ 13 , 14 ]. A complex file was then generated by merging the topology file of the ligand and the protein.…”
Section: Methodsmentioning
confidence: 99%
“…The validity was confirmed by the low RMSD (< 2 Å) of the redocked ligand from the orientation of the cocrystallized ligand and the replication of observed interactions from the pdb structure. [32] Discovery Studio 2017 R2 client (Dassault Systèmes BIOVIA, (Discovery Studio Visualizer), (2017 R2 Client), San Diego: Dassault Systèmes, ( 2017)) was used to analyze protein-ligand interactions.…”
Section: Molecular Dockingmentioning
confidence: 99%